2012
DOI: 10.3892/ijmm.2012.1047
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ankylosing spondylitis-associated genes by expression profiling

Abstract: Ankylosing spondylitis (AS) is a chronic inflammation attacking the sacroiliac joints and the spine. Certain genes have been associated with the occurrence of AS. Gene chip data were utilized to recognize genes associated with AS for the association of the clinical diagnosis and the biomedical study. Microarray expression data of AS were acquired from the public microarray database GEO (gene expression omnibus), and AS-related genes were obtained by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In fact, inhibition of the ITGA6 gene led to the suppression of tumor angiogenesis and gallbladder cancer growth [72]. ITGA6 has been previously identified as part of the differential expression profile of rheumatoid arthritis, and it was among the most differentially expressed genes in a murine model of AS [73,74]. Similarly, the CD2 gene encodes a cell adhesion molecule that is expressed on the surfaces of natural killer cells and T cells as well as some subpopulations of normal B cells [75].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, inhibition of the ITGA6 gene led to the suppression of tumor angiogenesis and gallbladder cancer growth [72]. ITGA6 has been previously identified as part of the differential expression profile of rheumatoid arthritis, and it was among the most differentially expressed genes in a murine model of AS [73,74]. Similarly, the CD2 gene encodes a cell adhesion molecule that is expressed on the surfaces of natural killer cells and T cells as well as some subpopulations of normal B cells [75].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several researchers carried out whole genome expression profiling analyses comparing AS patients to healthy donors [ 11 – 13 ]. These studies found that AS has a strong association with HLA-B27, and other non-HLA susceptibility genes, such as IL23R and ERAP1 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%